(untitled) (Andamios, Revista de Investigación Social, 2011)
With this work I try to introduce in the relation between memory and identity, personal and collective, to understand the changes these concepts suffers in the beginning of the 21’th Century. Pursuing this aim, I read again the major thinkers on the subject: from Locke to Proust, from Halbwachs to Baczko. With this lecture I put in question Ricoeur’s conclusions related to the role of imagination and truth in the construction of memory and identity, highlighting the constitutive function of fiction in this construction.